Еще раз о переводческих трансформациях - Армалите, Олимпия (Kalbotyra, 1987)
The article offers a revised approach to “translation transformation”, a much-used term in the theory and practice of translation. A translation transformation proper should not be confused with a quasi-transformation which is nothing else but replacement of a unit of a source language text by an interlingual equivalent in the target language.A translation transformation is viewed as a departure from an interlingual equivalent. An interlingual equivalent is not synonymous with a translation equivalent. Translation equivalents proper result from translation transformations. Yet there can be instances when translation equivalents coincide with interlingual equivalents.